Brood as booty: the effect of colony size and resource value in social insect contests. (4th March 2022) - Chapin, Kenneth James; Paat, Victor Alexander; Dornhaus, Anna
Abstract: Animals engage in contests for access to resources like food, mates, and space. Intergroup contests between groups of organisms have received little attention, and it remains unresolved what information groups might use collectively to make contest decisions. We staged whole-colony contests using ant colonies ( Temnothorax rugatulus ), which perceive conspecific colonies as both a threat and resource from which to steal brood. We recorded individual behaviors and used demographic characteristics as proxies for resource value (number of brood items) and fighting ability (number of workers). We found that ants altered their fighting effort depending on the relative number of workers of their opponent. Although the proximate mechanism for this ability remains uncertain, we found that colonies increased fighting when their opponent had relatively more brood, but not if opposing colonies had relatively many more workers. This suggests that ant colonies can use information about opposing colonies that shapes contest strategies. Further, the behavior of opposing colonies was strongly correlated with each other despite colony size differences ranging from 4% to 51%, consistent with the hypothesis that colonies can use opponent information. The behavior of a distributed, collective system of many individuals, like a eusocial insect colony, thus fits several predictions of contest models designed for individuals if we consider the gain and loss of worker ants analogous to energetic costs accrued during typical dyadic contests. Abstract : What information do social groups use in colony-wide warfare? We tested if, at the collective level, ant colonies use information about an opposing colony's demographics during contests over brood. We used the number of workers as a measure of colony fighting ability and the number of brood as a measure of colony resource value. We found that colonies use information about both the opposing colony's fighting ability and their own brood to make contest decisions.